Facile and Clean Solution Synthesis of Large-Scale ZnO Nanorods Assisted with Aliquat 336 - Qiang Huang; Jianping Liu (Journal of Chemistry)
A facile and clean fabrication of large-scale ZnO nanorods assisted with Aliquat 336 using aqueous chemical method is reported. As prepared, samples were characterized using XRD, EDS, SEM, TEM, and HRTEM. The optical properties were measured by Raman spectroscopy and room temperature photoluminescence spectra.